Exosome-Induced Regulation in Inflammatory Bowel Disease - Zhang, Huiting; Wang, Liang; Li, Changyi; Yu, Yue; Yi, Yanlin; Wang, Jingyu; Chen, Dapeng (Frontiers in Immunology, 2019)
An exosome (30–150 nm size) is a cell-derived vesicle. Exosome-induced regulation in inflammatory bowel disease (IBD) is becoming increasingly popular due to their potential functions of exosomal pathways. Exosomes, which are involved in the regulation of IBD, can be released from various cell types, or found in many physiological fluids, and plants. The specific functions of exosomes in IBD primarily depend on the internal functional components, including RNAs, proteins and other substances. However, exosome-induced transport mechanisms involving cell-cell communications or cell-environment interactions are also very important. Recent studies have revealed that exosome cross-talk mechanisms may influence major IBD-related pathways such as immune responses, barrier functions, and intestinal flora. This review highlights the advancements in the biology of exosome secretions and their regulation in IBD. The functional roles of exosomal components including nucleic acids, proteins, and some other components are the main focus of this review. More animal and clinical researches are needed to study the functions of exosomes on IBD. Designing new drug dosage form using exosome-like-structure may provide new insights into IBD treatment. This review suggests a potential significance for exosomes in IBD diagnosis and treatment.